Konstruksi Pemikiran Politik Ki Bagus Hadikusumo: Islam, Pancasila dan Negara - Suhartono dkk (Program Pascasarjana UMY, 2018)
Konstruksi Pemikiran Politik Ki Bagus Hadikusumo: Islam, Pancasila dan Negara